2021
DOI: 10.1002/ijgo.14066
|View full text |Cite
|
Sign up to set email alerts
|

Is pregnancy a risk factor for in‐hospital mortality in reproductive‐aged women with SARS‐CoV‐2 infection? A nationwide retrospective observational cohort study

Abstract: Objective To examine the effect of pregnancy on coronavirus disease 2019 (COVID‐19) ‐related in‐hospital mortality in women of reproductive age (between 15 and 45 years), with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection confirmed with polymerase chain reaction tests, adjusted for factors such as co‐infection and intervention that were not considered in existing literature. Methods Data gathered from a nationwide database in Brazil were analyzed using multivariate logistic regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…This was a cohort study of pregnant women with confirmed SARS‐CoV‐2 infection who were hospitalized in Brazil from the index case on 25 February 2020 to 29 November 2021. Data were obtained from SIVEP‐Gripe (Sistema de Informação de Vigilância Epidemiológica da Gripe), a Brazilian nationwide database, that has been described in more detail elsewhere 18 , 21 . Developed by the Federal Government of Brazil during the influenza pandemic in 2009, SIVEP‐Gripe aims to strengthen surveillance of severe acute respiratory syndrome‐related viral infection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was a cohort study of pregnant women with confirmed SARS‐CoV‐2 infection who were hospitalized in Brazil from the index case on 25 February 2020 to 29 November 2021. Data were obtained from SIVEP‐Gripe (Sistema de Informação de Vigilância Epidemiológica da Gripe), a Brazilian nationwide database, that has been described in more detail elsewhere 18 , 21 . Developed by the Federal Government of Brazil during the influenza pandemic in 2009, SIVEP‐Gripe aims to strengthen surveillance of severe acute respiratory syndrome‐related viral infection.…”
Section: Methodsmentioning
confidence: 99%
“…For deceased patients, the time from admission to recovery was recorded as ‘NA’ and omitted from the relevant analysis. If data were missing regarding signs, symptoms, history of exposure to animals, nosocomial infection or comorbidities, we assumed that characteristic to be absent 18 . Data on abnormal chest X‐ray were missing if imaging was not performed or registered.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The database has been the primary source of information on COVID-19-related hospital admission and deaths in Brazil, and has been described elsewhere. 7 …”
Section: Methodsmentioning
confidence: 99%
“…For any missing data on signs, symptoms (except for abnormal chest X-ray) or co-morbidities, the clinical condition was assumed to be absent, following the approach in previous studies with the same database. 7 , 17 Missing data of abnormal chest X-ray were excluded from the relevant analysis because imaging was not performed. Cases with ethnicity missing were also excluded from the corresponding analysis.…”
Section: Methodsmentioning
confidence: 99%